(untitled) (Physical Education, Health and Social Sciences, 2025)
This mixed‐methods study investigated how physical activity and personal resilience integrate into the Job Demands–Resources (JD–R) model to predict burnout and work engagement among remote employees (Bakker & Demerouti, 2007). A cross‐sectional survey of 350 teleworkers measured job demands, job resources, weekly physical activity, resilience (Connor & Davidson, 2003), burnout (Maslach et al., 1996), and engagement (Schaufeli & Bakker, 2004). As hypothesized, job demands correlated positively with burnout (r = .45, p < .001) and negatively with engagement (r = –.38, p < .001), while job resources correlated positively with engagement (r = .52, p < .001) and negatively with burnout (r = –.40, p < .001). Physical activity demonstrated a modest negative correlation with burnout (r = –.30, p = .002) and a positive correlation with engagement (r = .28, p = .004). Resilience was inversely related to burnout (r = –.35, p < .001) and positively related to engagement (r = .40, p < .001). Twenty semi‐structured interviews underwent reflexive thematic analysis (Braun & Clarke, 2006), yielding four themes: Digital Boundary Management, Movement as Resilience, Virtual Social Support, and Self‐Directed Recovery. Participants described how regular exercise routines and resilience practices mitigated stressors inherent in remote work, fostering higher engagement and lower exhaustion. These findings suggest that embedding physical activity and resilience‐building interventions within remote work policies can enhance well‐being and performance. Keywords: Integrating, Physical Activity, Resilience, Job Demands–Resources Model, Burnout, Work Engagement, Remote Employees